Current status of robotic assisted radical cystectomy with intracorporeal ileal neobladder for bladder cancer - Fahmy, Omar; Khairul Asri; Schwentner, Christian; Stenzl, Arnulf; Gakis, Georgios (Wiley Periodicals, 2015)
To investigate the current status and feasibility of robotic neobladder diversion after robotic assisted radical cystectomy. A Medline search was conducted resulting in identification of 423 articles. After exclusion of ineligible studies, 3 case series and 5 case reports were considered with a total number of reported cases of 203. Although robotic intracorporeal neobladder reconstruction is in its starting phase, initial perioperative results seem to be comparable to open series. However, randomized studies are needed to confirm non-inferiority.